Tackling Poverty through Women Empowerment: The Role of Social Capital in Indonesian Women’s Cooperative - Endah Widiyanti; Pudjihardjo Pudjihardjo; Putu Mahardika Adi Saputra (Universitas Negeri Malang, 2018)
Women in poverty discourse are considered as a highly vulnerable group. Women empowerment through micro-financing program is the appropriate way to solve the issue of woman poverty. Women, who often had difficult credit access in a formal financial institution, become facilitated in accessing capital to improve her business by the existence of woman cooperative (Koperasi Wanita). Cooperative is an organization who depicts social capital, which has important elements that refer to network, trust, and norm. The objective of this study was to found out the effect of network, trust, and norm as social capital dimension toward women empowerment and its impact toward poverty. This study used quantitative approach through questionnaire and documentation. The population of this study consists of members of Kelompok Pengusaha dan Pedagang Kecil (KPPK) Kopwan SU “Setia Budi Wanita” in East Java, with samples using 251 respondents. Based on Partial Least Square (PLS) analysis result, it showed that network, trust, and norm social capital dimensions has positive and significant effect toward women empowerment. Network, trust, and norm social capital dimensions have negative and significant effect toward poverty. And women empowerment has negative and significant effect toward poverty.Keywords: social capital, woman empowerment, poverty, cooperativeJEL Classification: I32, J16, O15, Z13